C-type lectins on macrophages participate in the immunomodulatory response to Fasciola hepatica products - Guasconi, Lorena (2011)
Fasciola hepatica releases excretory-secretory products (FhESP), and immunomodulatory properties have been described for the carbohydrates present in these parasite products. The interaction of FhESP with the innate immune cells, such as macrophages, is crucial in the early stage of infection. In this work we observed that peritoneal macrophages from naive BALB/c mice stimulated in vitro with FhESP presented: an increased arginase activity as well as Arginase I expression, and high levels of transforming growth factor-β and interleukin-10. A similar macrophage population was also observed in the peritoneum of infected mice. A partial inhibition of the immunomodulatory effects described above was observed when macrophages were pre-incubated with Mannan, anti-mannose receptor, Laminarin or anti-Dectin-1, and then stimulated with FhESP. In addition, we observed a partial inhibition of these effects in macrophages obtained from mice that were intraperitoneally injected with Mannan or Laminarin before being infected. Taken together, these results suggest the participation of at least two C-type lectin receptors, mannose receptor and Dectin-1, in the interaction of FhESP with macrophages, which allows this parasite to induce immunoregulatory effects on these important innate immune cells and may constitute a crucial event for extending its survival in the host.